STEM AS A GLOBAL EDUCATIONAL TREND - Hulai , Olha Ivanivna; Demchuk , Mariia Olehivna (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
The article reveals the essence and significance of STEM education as an important direction of modern educational policy around the world. Its advantages are analyzed, in particular, the integration of theoretical knowledge with practical skills, the development of critical thinking, communication skills and teamwork. The experience of implementing STEM education in leading countries, such as the USA, Great Britain, Finland, China, India, South Korea and Saudi Arabia, is considered. Special attention is paid to the implementation of the STEM approach in Ukraine in accordance with state strategic documents. The results of a survey of students of Lutsk National Technical University are presented, reflecting the level of awareness, perception and interest of young people in STEM areas.